Physical Characteristics and Stability of pH-Shifted Soybean Oil Body-Curcumin Composite Emulsion - KANG Mengxue, SUN Yufan, SONG Hanyu, ZHONG Mingming, WANG Shuai, QI Baokun (Shipin Kexue, 2023)
A curcumin delivery system was prepared by using the pH-shift method to load curcumin into the oil phase core of soybean oil body, which has a natural oil-in-water structure. The encapsulation characteristics of the emulsion were studied in terms of its encapsulation efficiency, particle size, zeta potential, and microstructure. The structural changes were analyzed by endogenous fluorescence spectroscopy and sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), and the storage stability, pH stability and oxidation stability were evaluated. The results showed that curcumin was successfully encapsulated with soybean oil body by the pH-shift method. At pH 1.0, the highest encapsulation efficiency of 65.55% was observed, and the lipid droplets were regular in shape and uniform in size, with an average particle size of 590.5 nm. The oxidative stability was good, but the storage stability and pH stability were poor. Protein structure was not changed significantly compared to untreated oil body. This study may provide a reference for future research on natural oil body to carry lipophilic polyphenols such as curcumin.